Relationship Between Sodium Consumption Patterns and Hypertension Incidents in the Elderly in the Work Area of the Wirang Public Health Center - Wiliani, Erma; Tasalim, Rian; Latifah; Irawan, Angga (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Hypertension is a common health issue among the elderly, with prevalence increasing as age advances. According to the WHO, approximately 1.13 billion people worldwide suffer from hypertension, with the elderly being the most vulnerable group. Poor hypertension management can lead to serious complications such as stroke, heart failure, and chronic kidney disease. Medication adherence is crucial in preventing such complications. However, elderly individuals with low educational attainment often struggle to understand medical instructions and the importance of consistent medication use. This study aims to analyze the relationship between education level and adherence to hypertension treatment among the elderly in the working area of Puskesmas Datah Kotou, Puruk Cahu. Method: This study used a quantitative research design with a cross-sectional approach. The sample consisted of 30 elderly individuals diagnosed with hypertension. Data were collected using a questionnaire measuring education level and adherence, assessed through the Morisky Medication Adherence Scale (MMAS-8). Correlation analysis was used to evaluate the data. Result: A total of 83.3% of respondents had a low level of education (elementary school), and 63.3% showed low adherence to treatment. Statistical analysis revealed a significant relationship between education level and treatment adherence, with a correlation coefficient of 0.691 and a p-value of 0.000. Conclusion: The study concludes that education level significantly affects the adherence of elderly individuals to hypertension treatment, highlighting the need for more effective health education interventions.